Flood risk to commercial property: Training and education needs of built environment professionals. Issue 4 (8th October 2018) - Bhattacharya-Mis, Namrata; Lamond, Jessica; Montz, Burrell; Kreibich, Heidi; Wilkinson, Sara; Chan, Faith; Proverbs, David
Abstract : Purpose: Improved management of commercial property at risk from flooding may result from well-targeted advice from built environment (BE) professionals, such as surveyors, valuers and project managers. However, research indicates that the role of these professionals in providing such advice is currently limited for a variety of reasons. This paper aims to investigate the (perceived and real) barriers and opportunities for providing such advice in a number of international locations. In particular, the research sought greater understanding of the link between regulation and guidance; perceived roles and capacity; and training and education needs. Design/methodology/approach: To cover different international settings, an illustrative case study approach was adopted within the selected countries (Australia, UK, USA, China and Germany). This involved a qualitative approach using semi-structured interviews of BE professionals with experience of advising on commercial properties at risk of flooding. Due to the specific nature of these interviews, a purposive sampling approach was implemented, leading to a sample of 72 interviews across the five international locations. Findings: Perceived barriers were linked to regulatory issues, a shortage of suitably experienced professionals, a lack of formal guidance and insurance requirements. BE professionals defined their roles differently in each case study in relation to these factors and stressed the need for closer collaboration among the various disciplines and indeed the other key stakeholders (i.e. insurers, loss adjusters and contractors). A shortage of knowledgeable experts caused by a lack of formal training, and education was a common challenge highlighted in all locations. Originality/value: The research is unique in providing an international perspective on issues affecting BE professionals in providing robust and impartial advice on commercial property at risk of flooding. While acknowledging the existence of local flood conditions, regulatory frameworks and insurance regimes, the results indicate some recurring themes, indicating a lack of general flood risk education and training across all five case study countries. Learning across case studies coupled with appropriate policy development could contribute toward improved skills development and more consistent integration of BE professionals within future flood risk management practice, policy and strategy.